2007
DOI: 10.1158/1078-0432.ccr-07-0110
|View full text |Cite
|
Sign up to set email alerts
|

Humanized Anti-CD26 Monoclonal Antibody as a Treatment for Malignant Mesothelioma Tumors

Abstract: Purpose: CD26 is a 110-kDa cell surface antigen with a role in tumor development. In this report, we show that CD26 is highly expressed on the cell surface of malignant mesothelioma and that a newly developed humanized anti-CD26 monoclonal antibody (mAb) has an inhibitory effect on malignant mesothelioma cells in both in vitro and in vivo experiments. Experimental Design: Using immunohistochemistry, 12 patients' surgical specimens consisting of seven malignant mesothelioma, three reactive mesothelial cells, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 86 publications
(120 citation statements)
references
References 30 publications
5
111
1
Order By: Relevance
“…The possibility of humanized anti-CD26 monoclonal antibody treatment for its inhibitory effect has been reported on malignant mesothelioma cell lines in vitro and in vivo experiments (12). This is the new promising strategy in antibody-based treatment of mesothelioma (12,13).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The possibility of humanized anti-CD26 monoclonal antibody treatment for its inhibitory effect has been reported on malignant mesothelioma cell lines in vitro and in vivo experiments (12). This is the new promising strategy in antibody-based treatment of mesothelioma (12,13).…”
Section: Discussionmentioning
confidence: 97%
“…(12), one of the a promising new developments for the antibody-based treatment of mesothelioma (12,13). CD26 is a widely distributed 110-kDa transmembrane glycoprotein with known dipeptidyl peptidase IV activity in its extracellular domain (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…18 For migration assay, a modified Boyden Chamber method was used. 19 In brief, 2.5 Ƃ 10 4 cells in 500 lL were seeded into the transwell insert chamber with a filter, and the inserts were placed in the lower chambers filled with 750 lL of RPMI-1640 containing 5% fetal calf serum. Chambers were incubated at 37 C under 5% CO 2 atm for 24 hours.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%
“…In vivo experimental xenograft models involving human MPM cells demonstrated that humanized anti-CD26 monoclonal antibody (YS110) treatment drastically inhibited tumor growth in tumor-bearing mice and reduced the formation of metastases, resulting in enhanced survival [13]. The active antimesothelioma agent PEM rapidly induces CD26 expression on the cell surface and inhibits in vivo tumor growth synergistically with YS110 [14].…”
Section: Humanized Anti-cd26 Monoclonal Antibody (Ys110) For the Treamentioning
confidence: 99%
“…The mechanisms of YS110 antitumor action for CD26-positive mesotheliomas are the following: (a) cell lysis of MPM cells via antibody-dependent cell-mediated cytotoxicity in addition to its direct antitumor effect via cyclin-dependent kinase (CDK) inhibitor p27 kip1 upregulation and disruption of binding to ECM [13]; (b) G1/S cell cycle arrest and G2/M cell cycle delay by upregulating CDK inhibitor p27 kip1 and p21 cip/ waf1 via multiple signaling pathways [13][14][15]; and (c) induction of nuclear translocation of cell-surface CD26 molecules by internalization of the CD26-YS110 complexes to inhibit proliferation of MPM cells via suppression of POLR2A gene expression [16]. The reduction of distant metastases by YS110 treatment in experimental models may be explained by CD26's function as a binding protein to distinct ECM proteins [13].…”
Section: Humanized Anti-cd26 Monoclonal Antibody (Ys110) For the Treamentioning
confidence: 99%